Should Indonesia Learn from Malaysia and Singapore’s Cross-Border Insolvency Asset Settlements? - Wijayanta, Tata; Adistia, Sheva Trisanda; Leonardus, Rado F; Hermawan, B.E (Yustisia, 2024)
The lack of boundaries between countries characterises the current globalisation. This convenience represents "high risk, high return", with the possibility of greater profits, but there is also a high risk of failure. This risk arises due to unpreparedness to mitigate the consequences of using technology or errors in its application, resulting in bankruptcy and affecting business actors and all assets. In Indonesia, the regulation of the cross-border insolvency mechanism still needs to be clarified, especially for cross-border assets that experienced difficulties in execution. This study examined Malaysia and Singapore's cross-border insolvency asset settlement arrangements as the closest countries to Indonesia. The study shows that Malaysia and Singapore have agreements with other countries formed as a collaborative step for settling bankruptcy cases. Indonesia is required to modify the principle of territorialism, either by forming bilateral or multilateral agreements, even by ratifying the UNCITRAL Cross-Border-Insolvency.